An integrated model of destination advocacy and its direct and mediating effects on destination revisit intention - Hossain, Md. Alamgir; Kalam, Abul; Hossain, Md. Shakhawat; Sarmin, Mst Nilima; Nuruzzaman, Md. (Business, Management and Economics Engineering, 2022)
Purpose – Purpose of the study is to build an integrated model of tourist destination advocacy explaining how tourists’ revisit intention is affected by its direct and mediating effects, integrated with destination experience, tourist satisfaction, and destination image. Design/methodology/approach – Data is collected online using a self-administered structured questionnaire tool, and the survey is hosted in a Google Doc. SPSS and SEM-Amos are used to analyze the data (443 samples) after successful data cleaning and outlier elimination. Findings – All of the hypotheses were shown to be true in this investigation, with the exception of two. The findings confirmed that tourists’ destination experiences improve tourists’ satisfaction, destination advocacy and destination image but not destination revisit intention. The likelihood of revisit intention is significantly influenced by destination satisfaction and image. Furthermore, destination satisfaction, destination advocacy and destination image significantly mediate the link between destination experience and revisit intention. Originality/value – This study contributes to the existing literature on consumer behavior in tourist destinations, and would guide practitioners towards effective destination management. Research limitations – Due to the lack of control factors on the relationship between all predecessors, destination revisit intentions, and all of the data gathered from domestic visitors, the current study may have limited the applicability of its findings. Therefore, additional research is necessary to validate these results across a variety of samples in order to draw generalizations.